"Giving Back" to Jamaica: Experiencing Community and Conflict while Traveling with Diasporic Heart. Issue 1 (2nd January 2017) - Williams, Bianca C.
Abstract : What can African Americans and Jamaicans learn about race, diaspora, and difference as they encounter one another in tourist spaces? How do their nationalized understandings and performances of Blackness inhibit or facilitate the creation of diasporic community and connectivity? Based on ethnographic research in multiple cities in Jamaica and the United States, this article examines how a group of African American tourist women, and Jamaicans they meet while vacationing, explore similarities and interrogate differences in spaces I call "diasporic contact zones." As African Americans travel to Jamaica with "diasporic hearts" and with the intention of "giving back" through strategic consumption, some of the Jamaicans they meet respond by analyzing the classed and nationalized power differentials embedded in tourist exchanges. This investigation of imagined communities and diasporic contact zones points to the elasticity of race, and the role difference plays in the construction of diaspora.